Generalized metabolic bone disease and fracture risk in Rothmund-Thomson syndrome. (9th May 2017) - Cao, Felicia; Lu, Linchao; Abrams, Steven A.; Hawthorne, Keli M.; Tam, Allison; Jin, Weidong; Dawson, Brian; Shypailo, Roman; Liu, Hao; Lee, Brendan; Nagamani, Sandesh C.S.; Wang, Lisa L.
Abstract: Rothmund-Thomson syndrome (RTS) is a rare autosomal recessive disorder characterized by poikiloderma, small stature, sparse hair, skeletal abnormalities, increased risk of osteosarcoma, and decreased bone mass. To date, there has not been a comprehensive evaluation of the prevalence and extent of metabolic bone disease in RTS. Furthermore, the mechanisms that result in this phenotype are largely unknown. In this report, we provide a detailed evaluation of 29 individuals with RTS with respect to their metabolic bone status including bone mineral density, calcium kinetics studies, and markers of bone remodeling. We show that individuals with RTS have decreased areal bone mineral density. Additionally, we demonstrate that the presence of pathogenic variants in RECQL4 and low bone mineral density correlate with the history of increased risk of fractures. Using a RECQL4-deficient mouse model that recapitulates skeletal abnormalities seen in individuals with RTS, we demonstrate that generalized skeletal involvement is likely due to decreased osteogenesis. Our findings are clinically relevant as they may help in the risk stratification of patients with RTS and also in the identification of individuals who may benefit from additional surveillance and management of metabolic bone disease.